Family as modern institution (Fractal: Journal of Psychology, 2009)
Every institution is a socialization tool created by man with function of managing your own interpersonal relationships. Institution creates norm, law, legitimacy for individual’s behavior in society. It is also generator of stability and security in social exchanges. Considering family like an institution, it presents itself as the first institution with which individual has contact in life. However, changes occurred in the society have altered ways of social interaction inside the families, establishing new ways of relationship between individual and environment in and out of them. Such changes are important in the new signification of family while a social institution.